Two new species of Callulops (Anura: Microhylidae) from montane forests in New Guinea - Oliver, Paul; Richards, Stephen; Tjaturadi, Burhan (Zootaxa, 2012)
Two new species of microhylid frogs assigned to the genus Callulops are described from the mountains of New Guinea.Callulops fojaensis sp. nov. is known only from mid-montane forest in the Foja Mountains of Papua Province, IndonesianNew Guinea, and can be distinguished from congeners by the combination of moderate size, short limbs, slightly expandedfinger and toe discs, and uniform brown dorsal and lateral colouration. Callulops mediodiscus sp. nov. is known from asingle site in mid-montane forest in Southern Highlands Province, Papua New Guinea, and can be distinguished from allcongeners by its wide finger and toe discs, moderate size and short advertisement call. Description of these two new frogspecies brings the number of Callulops known to 18, of which at least nine are only known from montane regions (>1000 m above sea level).